A study on the interaction of feldspar and quartz with mixed anionic/cationic collector - Ibrahim, Ismail (2011)

(untitled)
Interaction studies of feldspar and quartz with a mixed cationic/anionic collector namely N-tallow 1,3–propylenediamine-dioleate (duomeen TDO) were carried-out. The interaction between collector and minerals has potential to change the surface properties from hydrophilic to hydrophobic. In this study the adsorption behaviour of duomeen TDO on feldspar and quartz was assessed through zeta potential (ζ) and contact angle (Ө) measurement as well as with Fourier transformed infra-red (FTIR) spectroscopy. The sample was collected from Apex Granite, Muar, Johor and thus sample characterization were also carried out such as X-ray diffraction (XRD) was used for qualitative analysis and field emission scanning electron microscopy (FESEM) in order to yield useful microscopic information. Zeta-potential results between pH 2 and pH 10 for feldspar and quartz were measured. When the zero negative value of quartz reached pH 2 the separation process of feldspar from quartz was more significant. By gradually adding duomeen TDO, the contact angle of feldspar and quartz were increased leading to enhance hydrophobicity, but decreasing its free energy and components (Lifshitz-van der Waals γsLW, Lewis electron-donor γs-, and Lewis electron-acceptor γs+). FTIR results showed that at various dosages of duomeen TDO, this collector adsorbed on feldspar and quartz surfaces in the bands characteristic of alkyl chains, vas (CH3), vas (CH2) and vs (CH2) groups between region of 3000-2800 cm-1. Moreover the intensity of the alkyl chain bands increased slightly higher for feldspar compared to quartz with increasing initial duomeen TDO concentration. Finally single mineral flotation tests using Hallimond tube were performed and it has been found that feldspar floatability increased with increasing concentration of duomeen TDO. | Adsorption | Feldspar | Quartz | Mixed Collector | Flotation |